Chronic total occlusion angioplasty: no more excuses. (October 2014) - Sapontis, James; Grantham, J Aaron
Chronic total occlusion percutaneous intervention (CTO-PCI) technique has evolved coincident with improvements in success rate and safety of the procedure. Despite this, many patients are not offered this treatment even after medical therapy fails to alleviate their symptoms. The frequently stated reasons for this include the absence of randomized trial data, excessive costs and the time burden of the procedures. In this article our aim is to dispel the myths surrounding the benefits, costs and time burden of CTO-PCI and suggest that these excuses for not attempting CTO-PCI should be avoided so that patients receive the treatment they need, not simply the treatment their provider or institution prefers.